Pharmacogenetic variability of tuberculosis biomarkers in native and mestizo Peruvian populations - Luis Jaramillo‐Valverde; Kelly S. Levano; David D. Tarazona; Silvia Capristano; Cesar Sanchez; Julio A. Poterico; Eduardo Tarazona‐Santos; Heinner Guio (Pharmacology Research & Perspectives, 2024)
Abstract In Peru, 29 292 people were diagnosed with tuberculosis in 2022. Although tuberculosis treatments are effective, 3.4%–13% are associated with significant adverse drug reactions, with drug‐induced liver injury (DILI) considered the most predominant. Among the first‐line antituberculosis drugs, isoniazid is the main drug responsible for the appearance of DILI. In liver, isoniazid (INH) is metabolized by N‐acetyltransferase‐2 (NAT2) and cytochrome P450 2E1 (CYP2E1). Limited information exists on genetic risk factors associated with the presence of DILI to antituberculosis drugs in Latin America, and even less is known about these factors in the native and mestizo Peruvian population. The aim of this study was to determine the prevalence of NAT2 and CYP2E1 genotypes in native and mestizo population. An analytical cross‐sectional analysis was performed using genetic data from mestizo population in Lima and native participants from south of Peru. NAT2 metabolizer was determined as fast, intermediate and slow, and CYP2E1 genotypes were classified as c1/c1, c1/c2 and c2/c2, from molecular tests and bioinformatic analyses. Of the 472 participants, 36 and 6 NAT2 haplotypes were identified in the mestizo and native population, respectively. In mestizo population, the most frequent NAT2*5B and NAT2*7B haplotypes were associated with DILI risk; while in natives, NAT2*5G and NAT2*13A haplotypes were associated with decreased risk of DILI. For CYP2E1, c1/c1 and c1/c2 genotypes are the most frequent in natives and mestizos, respectively. The linkage disequilibrium of NAT2 single nucleotide polymorphisms (SNPs) was estimated, detecting a block between all SNPs natives. In addition, a block between rs1801280 and rs1799929 for NAT2 was detected in mestizos. Despite the limitations of a secondary study, it was possible to report associations between NAT2 and CYP2E alleles with Peruvian native and mestizo by prevalence ratios. The results of this study will help the development of new therapeutic strategies for a Tuberculosis efficient control between populations.